Pengaruh Metode Hypnoteaching terhadap Hasil Belajar Ilmu Pengetahuan Alam dan Sosial Siswa Kelas IV Sekolah Dasar Negeri 101949 Desa Pematang Tatal - Nidaul Hasanah; Emy Hariati; Nizmi Putri (Medan Resource Center, 2026)
This study investigated the effect of the hypnoteaching method on the Science and Social Studies learning outcomes of fourth-grade students at Public Elementary School 101949 Desa Pematang Tatal, Indonesia. The research was undertaken in response to persistently low student achievement and the predominance of teacher-centered instructional practices that limited student engagement. Employing a quantitative approach with a quasi-experimental design based on the Nonequivalent Control Group Design, the study involved 40 fourth-grade students, comprising 20 students in the experimental group and 20 students in the control group. Data were collected through pretest and posttest assessments and analyzed using tests of normality, homogeneity, and the independent samples t-test. The findings revealed that the experimental group achieved a higher mean posttest score (85.40) than the control group (73.15). Furthermore, hypothesis testing demonstrated that tcount (3.42) exceeded ttable (2.02) at the 0.05 significance level, indicating a statistically significant difference between the two groups. These findings demonstrate that the hypnoteaching method exerts a positive and significant effect on students' Science and Social Studies learning outcomes, suggesting that it represents an effective instructional approach for enhancing learning achievement and promoting more meaningful classroom engagement at the elementary school level.